A Multicenter Randomized Controlled Trial Comparing Single-Row With Double-Row Fixation in Arthroscopic Rotator Cuff Repair: Long-Term Follow-up. Issue 11 (September 2021) - Lapner, Peter; Li, Ang; Pollock, J. W.; Zhang, Tinghua; McIlquham, Katie; McRae, Sheila; MacDonald, Peter
Background: The long-term outcomes of single- versus double-row fixation in arthroscopic rotator cuff repair are not currently known. Purpose: To compare the treatment effects of the single- versus double-row suture technique in arthroscopic rotator cuff repair of full-thickness tears at 10-year follow-up. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Patients were evaluated at 10 years postoperatively. The primary outcome measure was the Western Ontario Rotator Cuff Index (WORC). Secondary outcome measures included the American Shoulder and Elbow Surgeons (ASES) score, Constant score, strength, and incidence of revision surgery. Ultrasound was used to evaluate the rotator cuff to determine repair integrity. Statistical analyses consistent with those of the main trial were conducted. Results: Of the original 90 participants, 77 (85%) returned at a mean follow-up of 10 years. At ten year follow-up, the WORC score was higher in the double row group (79.9 [95% CI, 16.2 to 99.1]) compared with the single row group (72.9, [95% CI, 4.3 to 100]), P = .020. From baseline to 2 years, the mean change in WORC scores for the single-row group was –48.5 compared with −40.6 for the double-row group, with a between-group difference of −7.8 (95% CI, −20.4 to 4.7). From 2 to 10 years, the change in WORC scores for the single-row group was 11.5 compared with −0.2 for the double-row group, with a between-group difference of 11.7 (95% CI, −0.7 to 24.3). From baseline to 10 years, the mean between-group difference was 3.9 (95% CI, −7.8 to 15.6). Similarly, a decrease in ASES scores was observed between 2 and 10 years for the single-row group (9.2 [95% CI, 0.9 to 17.5]; P = .029), with a nonsignificant decrease in ASES scores for the double-row group (6.2 [95% CI, −3.2 to 15.6]; P = .195) as well as a decrease in Constant scores for both the single- (9.5 [95% CI, 1.4 to 17.5]; P = .020) and double-row (14.4 [95% CI, 5.6 to 23.3]; P = .001) groups. Overall, 3 participants developed a full-thickness tear after 2 years: 2 from the double-row group and 1 from the single-row group. One participant from each study group underwent revision surgery after the 2-year time point. Conclusion: A statistically significant (but likely not clinically important) difference in WORC scores was seen at 10-year follow-up in favor of double-row fixation. Between baseline and 10-year follow-up, a decrease in most outcome scores was observed in both the single- and the double-row groups. Registration: NCT00508183 (ClinicalTrials.gov identifier).